Application of the pseudo-plaque assay for detection and titration of Crimean-Congo hemorrhagic fever virus - Berber, Engin; Canakoglu, Nurettin; Yoruk, Mustafa D.; Tonbak, Sukru; Aktas, Munir; Ertek, Mustafa; Ozdarendeli, Aykut (Elsevier Science Bv, 2013)
A pseudo-plaque assay was developed for detection and quantitation of Crimean-Congo hemorrhagic fever virus Turkey-Kelkit06. Enzyme-catalyzed color development of infected cells probed with anti-Crimean-Congo hemorrhagic fever virus antibodies was used for determining the titer of Crimean-Congo hemorrhagic fever Turkey-Kelkit06 and for its detection in samples from persons infected with the Crimean-Congo hemorrhagic fever virus. The pseudo-plaque assay accuracy was confirmed by comparing pseudo-plaque assay titers with fluorescent immunofocus assay and focus formation assay titers using three stocks of virus. No significant difference in virus titers of Crimean-Congo hemorrhagic fever Turkey-Kelkit06 among the three methods was observed. The pseudo-plaque assay is more sensitive than the fluorescent immunofocus assay for detecting the virus in primary isolates of Crimean-Congo hemorrhagic fever virus collected from humans, but no difference in sensitivity between the two methods was observed in the cell-adapted strain of Crimean-Congo hemorrhagic fever Turkey-Kelkit06. The pseudo-plaque assay is suitable for titration of Crimean-Congo hemorrhagic fever Turkey-Kelkit06, which does not develop plaques, suggesting it may also be suitable for the detection of other viruses. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Titration; Detection; Crimean-Congo hemorrhagic fever; Turkey-Kelkit06; Pseudo-plaque assay